UJI TOKSISITAS DARI PENYALUT LAYAK MAKAN BERBASIS PATI SAGU (Metroxylon sagu) - Khairun Nisah (Universitas Islam Negeri Ar-Raniry, 2017)
A sago starch- based (Metroxylon sagu) edible coating with sago powder as a filler and glycerol as a plasticizer has been made.This research is expected to provide information about microbial sensitivity towards the sago starch- based edible coating which is eco-friendly and safe to be used. Requirements to determine food quality refers to the role of E.coli as a toxicity indicator to cause food damage. Toxicity testing of E. coli toward sago starch-based coating was conducted by using Kirby Bauer method. A standardized agar-disc paper diffusion procedure is one way to to determine antibiotic resistancy of bacteria. Bacterial resistancy toward antibiotics is determined by the diameter of inhibit zone formed. Microorganisms cultures requires media that contain nutrients and appropriate environment such as Nutrient Agar (NA). Based on E. coli toxicity testing conducted to the sago starch-based edible coating in 370C temperature and 48 hours of incubation, it is found that the edible coated has not anticeptic activity toward Escherichia coli because the inhibit zone is not formed on the sago starch- based coating. Therefore, the edible coating which has been made is healthy to be consumed.